Un modelo de análisis sintáctico, paso a paso - José Javier Mangado Martínez (Universidad de La Rioja, 2013)
In the present article the author, with over twenty-five years' experience in teaching syntax at a university level, explains the method followed in his teaching practice of syntax analysis. He does so step by step, that is, justifying each one of the successive stages, and he openly reflects on the epistemological and didactic principles involved in his approach. With the aim of consolidating the theory at issue he systematically applies it to the specific analysis of a complex sentence.